Predictors of Left ventricular Dysfunction (LVD) in patients with Acute Myocardial Infraction (AMI) undergoing primary percutaneous coronary intervention (PPCI) - Syed, Fayaz Mujtaba; Abro, Hakim Ali; Abro, Hoat Ali; Sheikh, Khalid Muhammad; Chandio, Sultan Ahmed; Dasti, Mashooq Ali; Ochani, Teesha; Gurbakhshani, Rushali; khatri, Pirathena (LIAQUAT MEDICAL RESEARCH JOURNAL, 2025)
Objective: Myocardial Infraction leading to significant myocardial damage if not promptly addressed. The Aim of this study is to determine the frequency and predictors and assessing the associated factors with LV Dysfunction in patients with AMI undergoing PPCI. Methodology: A Descriptive cross-sectional study conducted at department of Cardiology department of SICVD hospital Larkana for the period of six month on 340 patients. All the patients from the age range between 30-70 years old with confirmed diagnosed cases of AMI based on angiography and undergone PPCI were included in the study. Primary PCI procedures were performed by the cardiologists; pre- and post-procedure clinical and pharmacological management were kept uniform. Descriptive analysis was applied and association between LVD and various demographic and clinical characteristics assessed by conducting the Chi-square/ sample t-test/ Mann-Whitney U test appropriately. The statistical significance was considered =p-value<0.05. Results: There was a male majority in the sample, with 264 (77.6%) of these being male and 76 (22.4%) being female. Only 6 patients (1.8%) were under 30 years old, according to the age distribution. The mean age score for patients with intact LVEF (>50%) was 3.76, while the averages for gender and hypertension were 1.23 and 1.36, respectively. The mean age of those with slightly decreased LVEF (40–50%) was 3.85, whereas the averages for gender and hypertension were 1.23 and 1.32, respectively. Conclusion A significant percentage of patients experience severe LV systolic dysfunction, which is linked to unfavourable clinical outcomes. significant LV systolic dysfunction after PPCI is independently predicted by larger myocardial infarction, renal impairment, and significant coronary artery disease.